Elastic-waveform inversion and imaging of 2010 walkaway VSP data from the Raft River geothermal field. (July 2021) - Li, David; Huang, Lianjie; Chi, Benxin; Gao, Kai; Jones, Clay; Moore, Joseph; Zheng, Yingcai
Highlights: Imaging results show subsurface layers and complex structures that are consistent with the geology (complex fabric) of the both the basement rock and overlying sediment at the Raft River geothermal field. Both PP and PS migration images show good correspondence between the lithology encountered in the wellbore with the locations of major reflectors away from the wellbore. The dips on the VSP migration images along each of the walkway line are consistent with the East dip of the basement rock at the Raft River geothermal field. Automatic fault detection on the VSP migration images using a machine learning method reveals many possible faults/fracture zones within the imaging regions. Abstract: A vertical seismic profiling (VSP) survey conducted in 2010 in the original RRG-9 well at the Raft River geothermal field is to understand the subsurface geologic structures for geothermal reservoir characterization. This survey consists of 40 three-component (3C) geophones deployed in the upper 600 m of the well and 255 vibroseis sources positioned along eight walkaway lines at the surface. We perform elastic-waveform inversion and reserve-time migration of the VSP data to obtain high-resolution subsurface images. We first process the raw walkaway 3C VSP data and separate the upgoing compressional-to-compressional (PP) and compressional-to-shear (PS) wavefields. We then build an initial velocity model based on sonic logging and zero-offset VSP data, update the initial model with first-arrival traveltime tomography, and refine the model using elastic-waveform inversion to reveal high-resolution velocity variations. We finally apply reverse-time migration to the upgoing wavefields to obtain high-resolution PP and PS migration images of the lithologies encountered in the well. The refined velocity models obtained using elastic-waveform inversion improve the subsurface migration imaging results. Our elastic-waveform inversion and reverse-time migration confirm the lithology interfaces revealed from well logs and provide images of subsurface geologic layers away from well RRG-9 at the Raft River geothermal field.